Professional DCOM programming : - Grimes, Richard (Wrox press, 1997)
DCOM -- the Distributed Component Object Model -- is a recent upgrade of a time-honored and well-tested technology promoted by Microsoft for distributed object programming. Now that components are playing a larger and larger part in Windows 98, Windows NT 4.0, and Windows 2000, every Windows programmer will want to understand the technology. DCOM competes with CORBA as a rich and robust method for creating expandable and flexible components, allowing you to plug in new parts conveniently and upgrade without the need for code changes to every program that uses your component.This book introduces C++ programmers to DCOM and gives them the basic tools they need to write secure, maintainable programs. While using Visual C++ development tools and wizards where appropriate, the author never leaves the results up to magic. The C++ code used to create distributed components and the communications exchanged between systems and objects are described at a level where the reader understands their significance and can use the insights for such tasks as debugging and improving performance.